2013
DOI: 10.1021/om4003957
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Uranium Dinitrogen Complex with Siloxide Supporting Ligands

Abstract: A new dinitrogen adduct of a homoleptic uranium tris(siloxide) complex, [U{OSi(Mes)3}3]2(μ-η2:η2-N2), is reported. Synthesis of the 15N-labeled isotopomer and Raman spectroscopy confirm the reductive activation of N2 to a (N2)2– dianion. The 15N NMR shift of the 15N2-labeled isotopomer is also reported. Crystallographic characterization shows a side-on (N2)2– coordinated in either an eclipsed or staggered conformation in different crystals. The U–N2–U complex is stable to vacuum and shows high thermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 85 publications
(167 reference statements)
0
48
0
Order By: Relevance
“…Due to the potential for the tetraphenylborate anion to engage in side reactions 22 in THF (Scheme 6) afforded an oily yellow-brown product to which was added one equivalent of 1, in the anticipation that a coordinated THF molecule would be displaced and the second uranium centre would bind (20) was isolated as pale green crystals, confirmed by a structural determination. 15b The dinuclear uranium(IV) cationic component consists of two essentially identical [U(Tren TMS )(THF)] + units bridged by a chloride anion whose U-Cl bond distances are not equivalent [2.887(2) and 2.918(2) Å], which suggests that the chloride is not equally associated with the uranium centres.…”
Section: Borate Derivativesmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to the potential for the tetraphenylborate anion to engage in side reactions 22 in THF (Scheme 6) afforded an oily yellow-brown product to which was added one equivalent of 1, in the anticipation that a coordinated THF molecule would be displaced and the second uranium centre would bind (20) was isolated as pale green crystals, confirmed by a structural determination. 15b The dinuclear uranium(IV) cationic component consists of two essentially identical [U(Tren TMS )(THF)] + units bridged by a chloride anion whose U-Cl bond distances are not equivalent [2.887(2) and 2.918(2) Å], which suggests that the chloride is not equally associated with the uranium centres.…”
Section: Borate Derivativesmentioning
confidence: 97%
“…It has also been shown that 11 can be independently prepared from 6 by reduction over a potassium mirror. 20 Treatment of trivalent 11 with neutral Lewis bases such as pyridine and hexamethylphosphoramide [(Me 2 N) 3 PO, HMPA] produces colour changes from purple to orange and black, respectively, affording [U(Tren DMBS )(C 5 H 5 N)] (13) and [U(Tren DMBS )-{OP(NMe 2 ) 3 }] (14), Scheme 3. The identity of the new complex was confirmed by a structural determination, performed on dark red crystals grown from pentane, to be the novel side-on bridging dinitrogen complex [{U(Tren DMBS )} 2 (m-Z 2 :Z 2 -N 2 )] (12), which was the first f-block dinitrogen complex.…”
Section: Uranium(iii) Derivativesmentioning
confidence: 99%
“…of HOSi(Mes) 3 were carried out in arene or n-hexane solvent (Scheme 199). In both cases, the compound (-2 : 2 -N 2 )[U{OSi(Mes) 3 } 3 ] 2 was formed, alongside other new byproducts, as observed by in situ 1 H NMR spectroscopy [163].…”
Section: Organolanthanides In Materials Sciencementioning
confidence: 78%
“…[(η ; however, recent studies by Arnold and co-workers have shown that N-N bond lengths determined using X-ray diffraction experiments can be underestimated and so may not provide the best way of assessing the level of dinitrogen reduction [87,88]. Both the Sm-N/C bond lengths and the Since this landmark discovery, the methodology of using reducing divalent rare earth metal complexes to activate N2 has resulted in analogous cyclopentadienyl complexes of Dy (5, 6) [74] and Tm (7,20) [75].…”
Section: Cyclopentadienyl Ancillary Ligandsmentioning
confidence: 99%
“…The most robust actinide N2 complex prepared to date is [{(Mes)3SiO}3U]2(μ-η 2 :η 2 -N2) (76) (Mes = 2,4,6-Me-C6H2) and is stable both in vacuo and in toluene solution up to 100 °C, at which point U{OSi(Mes)3}4 is slowly formed as the major product (52% conversion after 18 h) [87]. 76 is isolated from the reaction of U{N(SiMe3)2}3 with 3 equivalents of HOSi(Mes)3 under an N2 atmosphere (1 atm).…”
Section: Complexes Containing An Activated N2 Ligandmentioning
confidence: 99%